Hubungan Kecemasan, Depresi Dan Stres Dengan Kualitas Tidur Mahasiswa Fakultas Kedokteran Selama Pandemi Covid-19 - Nida Faradisa Fauziyah; Khatifah Nur Aretha (Universitas Muhammadiyah Purwokerto, 2021)
Coronavirus disease 2019 (COVID-19) is a sustainable health problem in 200 countries around the world. Public health emergency condition during pandemics such as SARS, MERS and Ebola are associated with increased psychological distress in the affected population. Negative impacts such as anxiety, depression and stress on students may become a burden on the mental and emotional health of students which in turn will affect the quality of student sleep. The author was interested in knowing about the relationship between anxiety, depression and stress with the quality of sleep of medical students during the COVID-19 pandemic. This study used an analytic observational study design with a cross sectional approach. This study was conducted in December with 81 students as respondents. This study used the DASS-42 questionnaire to measure anxiety, depression, stress and the PSQI to measure sleep quality. The results showed that 32.1%, 27.2%, 42% and 48.1% of students experienced anxiety, depression, stress and poor sleep quality. Statistical data measurement was done by using logistic regression, the results obtained p value = 0.030 (OR 3.967, 95% CI [1.143-13.722]), p = 0.004 (OR 11.456, 95% CI [2,217-59,196]), p = 0.043 (OR 0.314, 95 % CI [0.102-0.962]). From this study it can be concluded that anxiety, depression and stress had correlation with the sleep quality of students at the Faculty of Medicine, Muhammadiyah University of Surakarta during the COVID-19 pandemic.